PENGARUH CAPITAL ADEQUACY RATIO, LOAN TO DEPOSIT RATIO DAN UKURAN PERUSAHAAN PADA PROFITABILITAS BANK - Pranata, A.A Alit Wahyu Dwi (E-Jurnal Akuntansi, 2015)
The purpose of this study was to determine the effect of capital adequacy ratio, loan-deposit ratio and firm size on the profitability of banks in Indonesia Stock Exchange. The population used in this study is a banking company that is actively traded on the Indonesia Stock Exchange in 2009-2013. The samples used purposive sampling and through the specified criteria. The criteria used were the banking companies publish their financial statements in the Indonesia Stock Exchange and has the necessary data in the study variables. The method used in this study is the observation the behavior of non sourced from Indonesia Capital Market Directory (ICMD) year period from 2009 to 2013. This study uses the technique of multiple linear regression analysis with the results of testing the hypothesis that the Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) and company size has positive effect on the profitability of banks in Indonesia Stock Exchange.
Keywords: profitability; capital adequacy ratio; loan to deposit ratio; firm size.